Protocol for the Adaptation of a Direct Observational Measure of Parent-Child Interaction for Use With 7–8-Year-Old Children - Bennetts, Shannon K.; Love, Jasmine; Westrupp, Elizabeth M.; Hackworth, Naomi J.; Mensah, Fiona K.; Nicholson, Jan M.; Levickis, Penny (Frontiers in Psychology, 2021)
Objective. Parenting sensitivity and mutual parent-child attunement are key features of environments that support children’s learning and development. To-date, observational measures of these constructs have focused on children aged 2-6 years and are less relevant to the more sophisticated developmental skills of children aged 7-8 years, despite parenting being equally important at these ages. We undertook a rigorous process to adapt an existing observational measure for 7-8-year-old children and their parents. This paper aimed to: (i) describe a protocol for adapting an existing framework for rating parent-child interactions, (ii) determine variations in parents’ sensitive responding and parent-child mutual attunement (‘positive mutuality’) by family demographics, and (iii) evaluate the psychometric properties of the newly-developed measure (i.e. inter-rater reliability, construct validity). Method. Parent-child dyads completed one home visit, including a free-play observation and parent questionnaire. Dyads were provided with three toy sets: LEGO® Classic Box, Classic Jenga®, and animal cards. The Coding of Attachment-Related Parenting (CARP) was adapted for use with 7-8-year-old children, and rating procedures were streamlined for reliable use by non-clinician/student raters, producing the SCARP:7-8 Years. Trained staff rated video-recorded observations on 11 behaviors across two domains (five for parents’ sensitive responding, six for parent-child positive mutuality). Results. Data were available for 596 dyads. Consistently strong inter-rater agreement on the 11 observed behaviors was achieved across the 10-week rating period (average: 87.6%, range: 71.7% to 96.7%). Average ICCs were .77 for sensitive responding and .84 for positive mutuality. These domains were found to be related but distinct constructs (r=.49, p<.001). For both domains, average ratings were strongly associated with the main toy used during the observation (p<.001, highest: cards, lowest: LEGO®). Adjusted multivariate linear regression models (accounting for toy choice) revealed that less sensitive responding was associated with younger parent (p=.04), male parent (p=.03), non-English speaking background (p=.04), and greater neighborhood disadvantage (p=.02). Construct validity was demonstrated using six parent-reported psychosocial and parenting measures. Conclusion. The SCARP shows promise as a reliable and valid measure of parent-child interaction in the early school years. Toy selection for direct observation should be considered carefully in research and practice settings.